The Middle Path of Electoral Democracy: Direct Local Elections, Political Party Institutionalization, and the Local Democratic Deficit in Indonesia - Nawafi, Ahmad Yuzki Arifian (State Islamic Institute of Kudus (IAIN Kudus), 2026)
Indonesia’s electoral democracy is frequently criticized by framing direct local executive elections as the primary cause of democratic dysfunction at the local level. This article challenges this view by analyzing electoral democratic deficits through the relationship between direct elections and political party institutionalization. Direct local elections constitute a normative and constitutional achievement of democratic reform, reinforcing popular sovereignty and political participation. However, they operate within a weak institutional setting characterized by limited party accountability, fragmented representation, high-cost electoral competition, and the personalization of power. Drawing on a qualitative systematic literature review and the party institutionalization framework proposed by Randall and Svåsand, this study demonstrates that Indonesia’s electoral democratic deficit does not stem from the mechanism of direct elections itself, but from the limited institutional capacity of political parties to perform representative, leadership recruitment, and accountability functions. The article advances the concept of a middle path of electoral democracy that preserves direct elections while strengthening party institutionalization as a prerequisite for substantive, accountable, and sustainable constitutional democracy.